Evaluating the Suitability of English for International Tourism Using a Checklist Approach: A Study on ESP Learning Materials - Luciana; Abdul Syahid; Tria Angela Kusumaningrum (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2024)
This study aims to evaluate the effectiveness of the English for International Tourism Pre-Intermediate Student's Book in improving students' English language skills in the tourism sector. With the rapid growth of the tourism industry, there is a growing demand for professionals proficient in English. This textbook is designed to develop communication skills relevant to real-world scenarios. The study employs a systematic evaluation approach, focusing on the alignment of the material with industry needs, its relevance to professional contexts, and its impact on the development of students' language skills. Using qualitative analysis, the study examines the structure of the book, the authenticity of the materials, and its appropriateness for communication in tourism. The results reveal that the textbook offers significant advantages, including authentic content and strong relevance to the needs of the tourism industry. However, there are areas for improvement, such as greater variation in speaking exercises. This research contributes to the development of more effective ESP teaching materials for tourism education, ensuring that students acquire language skills that meet professional demands.